2010
DOI: 10.1074/jbc.m110.143461
|View full text |Cite
|
Sign up to set email alerts
|

RB·E2F1 Complex Mediates DNA Damage Responses through Transcriptional Regulation of ZBRK1*

Abstract: RB plays an essential role in DNA damage-induced growth arrest and regulates the expression of several factors essential for DNA repair machinery. However, how RB coordinates DNA damage response through transcriptional regulation of genes involved in growth arrest remains largely unexplored. We examined whether RB can mediate the response to DNA damage through modulation of ZBRK1, a zinc finger-containing transcriptional repressor that can modulate the expression of GADD45A, a DNA damage response gene, to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 55 publications
3
26
1
Order By: Relevance
“…Moreover, the growing tumor requires the endoplasmic reticulum stress, as well as ischemia and hypoxia which initiate the endoplasmic reticulum stress for its own neovascularization and growth, for apoptosis inhibition [15]. It is well known that retinoblastoma proteins, retinoblastoma binding and associated proteins, as well as E2F transcription factors, cyclins, cyclin-dependent kinases and its inhibitors participate in controling cell cycling and proliferation and are the components of endoplasmic reticulum stress system [14,15,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the growing tumor requires the endoplasmic reticulum stress, as well as ischemia and hypoxia which initiate the endoplasmic reticulum stress for its own neovascularization and growth, for apoptosis inhibition [15]. It is well known that retinoblastoma proteins, retinoblastoma binding and associated proteins, as well as E2F transcription factors, cyclins, cyclin-dependent kinases and its inhibitors participate in controling cell cycling and proliferation and are the components of endoplasmic reticulum stress system [14,15,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…This protein negatively regulates the G1-S transition by binding to the E2F transcription factors, until cyclin-dependent kinases phosphorylate retinoblastoma protein, causing E2F release. Moreover, retinoblastoma-E2F1 complex plays a critical role in ZBRK1 transcriptional repression, and loss of this repression may contribute to cellular sensitivity of DNA damage, ultimately leading to carcinogenesis [20]. Active E2F1/DP1 promotes apoptosis in both p53-dependent and independent manner, induces the expression of ADP rybosylation factor which, in turn, blocks MDM2-mediated ubiquination of p53, or enhances p53 transcriptional activity via direct binding of E2F1 to p53 [21].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the original findings, it has been recently shown that CtIP/CtBP plays a transcriptional co-repressor role in ZBRK1 expression. ZBRK1 is a zinc finger-containing transcriptional repressor that can modulate the expression of GADD45A to induce cell cycle arrest in response to DNA damage (Liao et al 2010). It has been proposed that the contribution of RB to DNA damageinduced growth arrest may depend on the formation of this complex and loss of CtIP/CtBPmediated repression could affect the cellular sensitivity to DNA damage.…”
Section: Genome-wide Yeast Two-hybrid Interaction Screeningmentioning
confidence: 99%
“…The latter is involved in induction of cell cycle arrest in response to DNA damage (Siafakas and Richardson, 2009). E2F-1, but not other E2F proteins, binds to the ZBRK1 promoter, together with pRb, CtIP and CtBP, forming repressor complexes that interfere with ZBRK1 expression (Liao et al, 2010). In pRbdeficient cells, increased susceptibility to DNA damage induced by UV radiation or methylating agents occurs, partly as a result of abnormal cell cycle arrest and DNA repair.…”
Section: Introductionmentioning
confidence: 99%